(untitled) (World Economics and Finance Bulletin, 2026)
This article provides a comprehensive, evidence-based analysis of commercial Public-Private Partnerships (PPPs), drawing from international empirical studies, institutional reports from the World Bank, IMF, OECD, and academic literature. It explores the conceptual framework of commercial PPPs in revenue-generating sectors such as energy, transport, and telecommunications, contrasted with social infrastructure PPPs. Through case studies, comparative economic impacts, and GDP contributions, the analysis highlights efficiency gains, risk management challenges, and policy recommendations for emerging markets. Special attention is given to Uzbekistan’s PPP landscape up to 2026 projections. Key findings underscore commercial PPPs’ role in driving 1-3% GDP growth via productivity multipliers, while emphasizing the need for robust governance to mitigate renegotiations.